Implementation of Social Media Analytics Using Buffer Tool to Measure Business Instagram Content Performance - Yohana, Yohana; Kosasi, Sandy; Yuliani, I Dewa Ayu Eka (LPPM Universitas Potensi Utama, 2025)
Instagram social media has been utilized by businesses as a platform for digital marketing activities. To assess the success of these marketing efforts, measuring content performance on Instagram is essential. This measurement involves analyzing data and insights regarding metrics such as reach, engagement, and impressions. These metrics are obtained through the process of Social Media Analytics (SMA) on the Instagram platform. However, many businesses experience a consistent decline in insights, resulting in decreased effectiveness of digital marketing. This study proposes a solution by implementing enhanced digital marketing on Instagram, followed by the measurement of Key Performance Indicators (KPIs). The measurement tool used is Buffer, which provides a comprehensive analysis dashboard concerning content performance, audience interaction patterns, and the impact of posting times on audience engagement in real-time. The KPI measurement during 3 months results indicate a significant increase, including a 66% rise in posts, a 69% increase in impressions, a 32% increase in reach, a 167% increase in likes, a 90% increase in comments, and a 105% increase in new followers for Casia store's Instagram channel. The accuracy of the data obtained from the Buffer analytic tool is verified through comparison with the impression metrics from Instagram Insight, which show identical figure, and Buffer has proven to be effective and accurate for measuring content performance and supports the implementation of SMA on the Instagram platform.